Effectiveness of geriatric rehabilitation in inpatient and day hospital settings: a systematic review and meta-analysis - Eric K. C. Wong; Peter M. Hoang; Andrew Kouri; Sandeep Gill; Yu Qing Huang; Janice C. Lee; Sophie M. Weiss; Raymond Daniel; Jessie McGowan; Krystle Amog; Joanna E. M. Sale; Wanrudee Isaranuwatchai; et al. (BMC Medicine)
Abstract Background Geriatric rehabilitation is a multidisciplinary intervention that promotes functional recovery in older adults. Our objective was to assess the efficacy of geriatric rehabilitation in inpatient and geriatric day hospital settings. Methods We searched MEDLINE, EMBASE, Cochrane Central Register of Controlled Trials, PsycINFO, PEDro and AgeLine from inception to September 30, 2022 for randomized controlled trials (RCTs) including older adults (age ≥ 65 years) undergoing geriatric rehabilitation (inpatient or day hospital) with a usual care comparator group. Primary outcome measures included mortality, long-term care home (LTCH) admission, and functional status. Secondary outcomes included discharge/remaining at home, functional improvement, length of stay, cognition, mood, and quality of life. Records were screened, abstracted and assessed for risk of bias (Cochrane Risk of Bias [RoB] 2) by two reviewers independently. We conducted a random effects meta-analysis to summarize risk ratios (RR, dichotomous outcomes) and standardized mean differences (SMD, continuous outcomes). Results Of the 5304 records screened, 29 studies (7999 patients) met eligibility criteria. There were 23 RCTs of inpatient geriatric rehabilitation (6428 patients) and six of geriatric day hospital (1571 patients) reporting outcomes of mortality (26 studies), LTCH admission (22 studies), functional status (19 studies), length of stay (18 studies), cognition (5 studies), mood (5 studies) and quality of life (6 studies). The primary outcome of mortality at longest follow up was lower in the rehabilitation group (RR 0.84, 95% confidence interval [CI] 0.76 to 0.93, I2 = 0%). LTCH admission was lower in the rehabilitation group at longest follow up (RR 0.86, 95% CI 0.75 to 0.98, I2 = 8%). Functional status was better in the rehabilitation group at longest follow up (SMD 0.09, 95% CI 0.02 to 0.16, I2 = 24%). Cognition was improved in the rehabilitation group (mean difference of mini-mental status exam score 0.97, 95% CI 0.35 to 1.60, I2 = 0%). No difference was found for patient length of stay, mood, or quality of life. Conclusions Geriatric rehabilitation in inpatient and day hospital settings reduced mortality, LTCH admission, and functional impairment. Future studies should explore implementation of this intervention for older adults. Review registration PROSPERO: CRD42022345078.